Rancang Bangun Aplikasi Travel Berbasis Android dengan Pendekatan Waterfall - Nabilah, Putri Khairunnisa; Alda, Muhammad; Aliyah Royani Siahaan, Melva; Kartika Barus, Shila; Ikhsan, M. Audi (Jurnal Ilmiah Teknologi Informasi Asia, 2024)
An Android-based travel application is designed to make it easier for users to plan their trips. This study focuses on the design of the application using the Waterfall approach, which includes needs analysis, UI/UX design, implementation, and design evaluation. This application offers features such as destination search, ticket booking, and accommodation with an easy-to-use interface. The results of user testing showed that 90% of users found the application navigation easy to understand, 85% were satisfied with the visual design, and 80% stated that the application features met their needs in planning their trips. However, around 15% of users provided input for improving the layout and adding supporting features. This study contributes to the development of a more efficient and user-friendly travel application, while also offering recommendations for further development to improve the overall user experience.